Kinship Terms in Arabic With a Contrastive Perspective on Croatian (Prilozi za orijentalnu filologiju, 2025)
This paper aims to examine kinship terminology in Modern Standard Arabic with a contrastive perspective on Croatian, and to analyze the familiarity and use of kinship terms in two urban centers: Damascus and Zagreb. Arabic features a highly differentiated system of kinship terms and possesses a rich, dynamic lexical inventory that remains active and productive in contemporary usage. This lexicon is closely tied to the patriarchal structure of Arab social, cultural, and religious life. Kinship relations pervade many aspects of everyday life, and the family – not only the nuclear but also the extended – continues to occupy a prominent place in the hierarchy of social values. The Croatian language also possesses a rich kinship lexicon; however, many of these terms are either unknown to or unused by native speakers, particularly in urban areas. The analysis in this study categorizes kinship terms according to gender (male/female), type of relation (blood/non–blood), generational difference (ascending/descending), and affiliation through the paternal or maternal line. A comparison of kinship terms in these two genetically and typologically distinct languages reveals that the gender of the referential person from whom kinship is defined (ego) is not a relevant factor in Arabic, whereas in Croatian, it often plays a crucial role in the selection of appropriate terms. Furthermore, Croatian lexicographic sources often diverge significantly from data obtained through questionnaires, a discrepancy not observed in Arabic. In both languages kinship terms are frequently used outside of familial contexts as forms of address and reference in social interaction.